1993
DOI: 10.1007/bf01324432
|View full text |Cite
|
Sign up to set email alerts
|

A baseline assessment of cigarette sales to minors in San Diego, California

Abstract: This study reports the sales rate of cigarettes to minors in San Diego County, and investigates factors associated with cigarette sales to minors. Two hundred and ninety-four stores were identified and recruited to participate in a retailer education effort. To assess the baseline illegal sales rate of cigarettes to minors, selected stores were surveyed by 70 volunteer teams of adults and minors. Questionnaires were also administered to participating store owners or managers to assess retailers' knowledge abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…As an example, consider that previous studies show girls have an easier time purchasing tobacco products from stores than boys; in fact, clerks more frequently encourage girls to buy cigarettes, and request identification less frequently from them than boys. [33][34][35] Race and ethnicity of clerks also influence tobacco sales to minors-African American clerks are less likely to sell to minors. 35 What this suggests is that the proper implementation and rigourous enforcement of photo identification and clerk intervention policies, both involving an active interaction between merchants and buyers, could be quite effective in deterring access to tobacco products, especially for initiators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, consider that previous studies show girls have an easier time purchasing tobacco products from stores than boys; in fact, clerks more frequently encourage girls to buy cigarettes, and request identification less frequently from them than boys. [33][34][35] Race and ethnicity of clerks also influence tobacco sales to minors-African American clerks are less likely to sell to minors. 35 What this suggests is that the proper implementation and rigourous enforcement of photo identification and clerk intervention policies, both involving an active interaction between merchants and buyers, could be quite effective in deterring access to tobacco products, especially for initiators.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Race and ethnicity of clerks also influence tobacco sales to minors-African American clerks are less likely to sell to minors. 35 What this suggests is that the proper implementation and rigourous enforcement of photo identification and clerk intervention policies, both involving an active interaction between merchants and buyers, could be quite effective in deterring access to tobacco products, especially for initiators. Indeed, photo identification was strongly associated with lower likelihood of initiation and adverse transition among low SES females.…”
Section: Discussionmentioning
confidence: 99%
“…The gender difference in buying rate was somewhat surprising, in that a number of studies have demonstrated that underage girls are actually more successful at buying tobacco than boys 1018 21 However, just because girls can buy cigarettes does not mean that they do. Although the success rate per attempt may be lower for boys, through sheer persistence they may actually complete more purchases than do girls.…”
Section: Discussionmentioning
confidence: 99%
“…Given the exploratory nature of the site visits, we were inclusive in identifying variables that might be related to status as a case. These variables were largely identified through a review of studies involving site visits to sellers of cigarettes,15 16 17 18 19 alcohol20 21 22 23 24 25 and guns26 27 and preliminary visits to ∼30 retailers in Northern California. A few variables were included following the first ∼20 site visits conducted for the study.…”
Section: Methodsmentioning
confidence: 99%